1997
DOI: 10.1180/minmag.1997.061.404.11
|View full text |Cite
|
Sign up to set email alerts
|

Petrochemistry of a Late Precambrian garnetiferous granite, pegmatite and aplite, southern Israel

Abstract: Garnet is a widespread minor accessory mineral in the Late Proterozoic Elat-Quarry granite of southern Israel and is more abundant in the associated pegmatite and aplite. All garnets are dominated by almandine and spessartine end-members. Granite-hosted garnets are zoned with relative enrichment of Mn in the core and Fe in the rim. The chemistry of the garnet in the pegmatite and aplite are comparable to the rim compositions of garnets in the granite, but with a slight Fe-depletion at the rims. Geochemical par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…A prominent joint system cuts the body, striking approximately N45E. Elat Granite contains 1–3.5 ppm uranium [ Bogoch et al , 1997] and exhibits a radon level of 7.8 ± 4.3 kBq/m 3 at a depth of 0.5 m [ Shirav and Vulkan , 1997].…”
Section: Geographic and Geological Settingmentioning
confidence: 99%
“…A prominent joint system cuts the body, striking approximately N45E. Elat Granite contains 1–3.5 ppm uranium [ Bogoch et al , 1997] and exhibits a radon level of 7.8 ± 4.3 kBq/m 3 at a depth of 0.5 m [ Shirav and Vulkan , 1997].…”
Section: Geographic and Geological Settingmentioning
confidence: 99%
“…According to Green (1977), spessartine-rich garnets in rocks of granitoid composition show evidence of formation at low P-T. In granites (Bogoch et al, 1997), the almandine-spessartine magmatic garnets are commonly zoned either with increasing Fe relative to Mn from core to rime or vice versa, depending on the nature of the granitic magma and the crystallization conditions. The composition of the almandine-spessartine garnets in pegmatites and aplites is more stable not showing any significant zoning.…”
Section: Discussionmentioning
confidence: 99%
“…It is suggested that this is associated with a rather specific tectonic setting in the broad eastern Aegean area, including Kos-Samos-Patmos-Chios and Bodrum, in a zone extending broadly in a N S orientation, that is transverse to the modern volcanic arc. Manganese-rich garnets crystallize from magmas enriched in volatile constituents (Baldwin and von Knorring, 1983;Bogoch et al, 1997). According to Green (1977), spessartine-rich garnets in rocks of granitoid composition show evidence of formation at low P-T.…”
Section: Discussionmentioning
confidence: 99%
“…The magmatic origin of garnet in pegmatites and granites from the Wadi Shelomo pluton was justified by Bogoch et al (1997). Table 3 Microprobe analyses of muscovite from the EG and SGG (wt.%) The distinctions in chemical compositions of the minerals from magmatic and metamorphic rocks are significant.…”
Section: Mineral Chemistrymentioning
confidence: 99%